Cape Verdean blues - Barbosa, Shauna (Pittsburgh, Pa. : University of Pittsburgh Press, 2018)
The speaker in Cape Verdean Blues is an oracle walking down the street. Shauna Barbosa interrogates encounters and the weight of their space. Grounded in bodily experience and the phenomenology of femininity, this collection provides a sense of Cape Verdean identity. It uniquely captures the essence of "Sodade," as it refers to the Cape Verdean American experience, and also the nostalgia and self-reflection one navigates through relationships lived, lost, and imagined. And its layers of unusual imagery and sound hold the reader in their grip
This Won't Make Sense in English kanalaLiberation; Acknowledgments.
Print version record.
JSTOR
Keywords: American poetry -- 21st century; FICTION -- General; POETRY -- American -- General; American poetry; 2000-2099; Poetry; poetry; Poetry; Poetry; Poésie.